Country risk, inflation, profitability, and firm value: Evidence from pharmaceutical firms - Anne Tonthawi; Bayu Indra Setia; Atang Hermawan (LPPM ISNJ Bengkalis, 2026)
This study examines the effect of inflation as a proxy for country risk on the profitability of pharmaceutical companies and its implications for firm value, with profitability positioned as a mediating variable. The research adopts an explanatory quantitative approach using balanced panel data from eight pharmaceutical companies observed over an eleven-year period (2014–2024). Inflation data are obtained from official national statistics, while profitability and firm value are measured using return on equity (ROE) and price-to-book value (PBV), respectively. Panel data regression with a fixed effects model is employed, and the mediating role of profitability is tested using a stepwise approach supported by the Sobel test. The findings reveal that inflation has a positive and significant effect on profitability, and profitability has a positive and significant effect on firm value. Furthermore, the Sobel test confirms that profitability partially mediates the effect of inflation on firm value, indicating both direct and indirect transmission mechanisms. These results suggest that pharmaceutical firms are able to adapt to inflationary pressures through operational efficiency and profitability enhancement, which are subsequently rewarded by the market. The study contributes theoretically by integrating macroeconomic risk and firm-level performance in explaining firm value, and practically by providing insights for managers, investors, and policymakers in formulating strategies to manage inflationary risks in the pharmaceutical sector.